Planting density and its effect on plant height and rosette quality in ornamental cabbages for cutting - Kim, Yoo Ree (2018)
Fil: Kim, Yoo Ree. Universidad de Buenos Aires. Facultad de Agronomía. Departamento Producción Vegetal. Cátedra de Floricultura. Buenos Aires. Argentina.